COVID-19 As a Public Health Problem, Recent Developments and Public Health Nursing - MEHMET UÇAR (Innovative Journal of Medical and Health Sciences, 2020)
The number of coronavirus-caused deaths is increasing and this is turning into a public health problem. The virus occurred in an open animal market in the People’s Republic of China. It infects people and is threatening the whole world. The number of deaths is gradually increasing. Health professionals are making efforts to solve this problem, thus they are at great risk. This situation, which has become a public health problem, lays a new burden on public health nurses. Such cases have increased in the 21st century and epidemics called SARS, MERS, avian influenza, swine influenza, and finally, COVID-19 have occurred. Governments and healthcare providers should take the necessary precautions and perform their tasks to prevent such outbreaks. All healthcare professionals, especially public health nurses, should provide training, counseling and preventive healthcare services on COVID-19 for the society. Governments should take necessary and sufficient measures to prevent the spread of such outbreaks and develop health policies. Key words: Public Health Nursing–COVID-19–Health Professionals–Preventation